PENGARUH KONSEP DIRI TERHADAP PERILAKU BULLYING PADA MAHASISWA DI UNIVERSITAS X - FELLIANTI MUZDALIFAH; HAFIZ BIMO AFRIYANTO (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2014)
This research aims to find out the influence of self-concepts towards bullying behavior among college student in â€œXâ€ University. The dependent variable in this study was bullying and independent variable in this study was the self concept.This research uses quantitative methods, data were obtained by using a questionnaire. William h. Fitts (1965), whereas the scale of bullying refers to the theory of Participant Questionnaire (PRQ) Role of Salmivalli (1996). Data processing using Rasch modeling with the help of winstep version 3.73 and hypothesis test using the SPSS version 16.0. The participants of this research were 71 college students in â€œXâ€ University. This research using a nonprobability sampling. The results of this research show that there was negative influences between self-concept toward bulying behavior of 23% and the remaining 77% influenced by other factors.